Administration of Microencapsulated Probiotic at Different Doses to Control Streptococcosis in Tilapia (Oreochromis niloticus) - DIAH AYU SATYARI UTAMI; WIDANARNI - WIDANARNI; M AGUS SUPRAYUDI (Microbiology Indonesia, 2015)
This study aimed to produce microencapsulated probiotic and determine its optimal dose to control streptococcosis in tilapia (Oreochromis niloticus). The probiotic used in this study was Bacillus sp. NP5 RfR that was encapsulated by sterile 10% maltodextrin solution and dried by spray dryer. The experimental fish were reared 28 days and fed by the administration of microencapsulated probiotic in feed with different doses (0,5% (A), 1% (B), and 2% (C)) which were 1010 CFU g-1 as the concentration and control without administration of microencapsulated probiotic, including negative (K-) and positive (K+) control. On day 30, all of the fish except K- were challenged by injecting 0.1 mL/fish Â of Streptococcus agalactiae (105 CFU ml-1) by intra-peritoneal (IP) route. This study showed that administration of 0.5% microencapsulated probiotic was effective to control streptococcosis in tilapia with higher post-challenge survival rate, better hematological parameter values, and could inhibit S. agalactiae growth in the host target organs.